2008
DOI: 10.1016/j.beproc.2008.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Contextual fear conditioning differs for infant, adolescent, and adult rats

Abstract: Contextual fear conditioning was tested in infant, adolescent, and adult rats in terms of Pavlovian conditioned suppression. When a discrete auditory conditioned stimulus (CS) was paired with footshock (unconditioned stimulus, US) within the largely olfactory context, infants and adolescents conditioned to the context with substantial effectiveness but adult rats did not. When unpaired presentations of the CS and US occurred within the context, contextual fear conditioning was strong for adults, weak for infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 41 publications
(71 reference statements)
5
38
3
Order By: Relevance
“…The authors speculated that this temporary suppression of contextual fear memory could serve an adaptive function, allowing adolescent mice to venture out of the nest and explore potentially threatening environments. In line with several previous studies in mice (Hefner and Holmes 2007) and rats (Pugh et al 1997;Brasser and Spear 2004;Esmoris-Arranz et al 2008;Murawski and Stanton 2010), however, we found no evidence of memory suppression in adolescents. Instead, we found that levels of conditioned fear were stable across all ages tested, from infancy to adulthood.…”
Section: Learning and Memorysupporting
confidence: 92%
See 1 more Smart Citation
“…The authors speculated that this temporary suppression of contextual fear memory could serve an adaptive function, allowing adolescent mice to venture out of the nest and explore potentially threatening environments. In line with several previous studies in mice (Hefner and Holmes 2007) and rats (Pugh et al 1997;Brasser and Spear 2004;Esmoris-Arranz et al 2008;Murawski and Stanton 2010), however, we found no evidence of memory suppression in adolescents. Instead, we found that levels of conditioned fear were stable across all ages tested, from infancy to adulthood.…”
Section: Learning and Memorysupporting
confidence: 92%
“…Although some studies report that rats fail to associate a shock with a context until 23-24 d of age (Spear 1979;Rudy 1993;Rudy and Morledge 1994;Raineki et al 2010;Schiffino et al 2011), others demonstrate that this type of learning can occur at 17-18 d of age under some training conditions (Brasser and Spear 2004;Esmoris-Arranz et al 2008;Pisano et al 2012) or following certain neonatal manipulations (i.e., injection of fibroblast growth factor-2, sensory stimulation) (Woodcock and Richardson 2000;Graham and Richardson 2010;Callaghan and Richardson 2011). Our finding that mice are able to associate a shock with a context as early as 13-14 d of age, however, suggests that brain and behavioral development is accelerated in mice compared to rats, consistent with previous proposals (Pellis and Iwaniuk 2000;Whishaw et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, contextual learning may emerge earlier than suggested by the “traditional view” (Brasser & Spear, 1998; Brasser & Spear, 2004; Esmorís-Arranz, Méndez, & Spear, 2008; Foster & Burman, 2010). Thus, it seems likely that several structures, and the connectivity between them, are continuing to emerge during the periweaning time period, making a strict dissociation between auditory and contextual fear conditioning somewhat unlikely.…”
mentioning
confidence: 91%
“…For example, when examining extinction of fear conditioning, Rick Richardson and colleagues report giving twice as many CS-US pairings to PD 16 subjects than to PD 23 subjects in order to achieve equivalent initial freezing, suggesting that PD 23 subjects otherwise demonstrate greater conditioning [32], [33]. Although they did not directly compare across ages, another study found that there is an almost 3-fold increase in freezing between PD 17 and 28 to a CS-context compound [25]. No such increase was found to the context alone, suggesting that CS-elicited freezing accounted for this effect.…”
Section: Introductionmentioning
confidence: 99%